Brand Loyalty Mediation in Brand Attachment and Customer Digital Experience towards Smartphone Repurchase Intentions - Cornelia, Verina; Pasharibu, Yusepaldo (Benefit: Jurnal Manajemen dan Bisnis, 2020)
Brand loyalty is one of the most essential component that incumbent company to retain their customers, particularly in order to win the market share. The main reason is that incumbent firms need to maintain their market share and then upscale their market when they have a thorough understanding of the segmentation. Brand loyalty in this study is utilized as a mediating variable to confirm the impact of brand attachment and customer digital experience for the repurchase intention creation of smartphone users.Â  An online questionnaire was distributed to 100 respondents using a purposive sampling technique. The criteria of respondents in this study are those who are using Samsung smartphone for at least a year, and experience searching the brand using a digital platform. The statistical analysis showed that brand attachment and customer digital experience have a significant positive influence on brand loyalty. Furthermore, brand attachment shows direct and indirect effects to repurchase intentions indicating partial mediation existence of brand loyalty.Â  Customer digital experience indirectly affects repurchase intentions through brand loyalty. These results highlight the role of brand attachment and customer digital experience has to secure repurchase intentions of customers by utilizing brand loyalty.